Association Between Promoter Polymorphisms in CD46 and CD59 in Kidney Donors and Transplant Outcome - Michielsen, Laura A.; van Zuilen, Arjan D.; Kardol-Hoefnagel, Tineke; Verhaar, Marianne C.; Otten, Henny G. (Frontiers in Immunology, 2018)
Complement regulating proteins, including CD46, CD55 and CD59, protect cells against self-damage. Because of their expression on the donor endothelium, they are hypothesized to be involved in accommodation. Polymorphisms in their promoter regions may affect their expression. The aim of this study was to investigate if donor polymorphisms in complement regulating proteins influence kidney transplant outcomes. We included 306 kidney transplantations between 2005 and 2010. Five polymorphisms in the promoters of CD46, CD55 and CD59 were genotyped. A CD59 promoter polymorphism (rs147788946) in donors was associated with a lower one-year rejection-free survival (adjusted HR 2.18, 95%CI 1.12-4.24) and a trend towards impaired 5-year graft survival (p=0.08). Patients receiving a kidney with at least one G allele for the CD46 promoter polymorphism rs2796267 (A/G) showed a lower rejection-free survival, though this became borderline significant after adjustment for potential confounders (HR1.87, 95% CI 0.96-3.65). A second CD46 promoter polymorphism (rs2796268, A/G), was also associated with a lower freedom from acute rejection in the presence of at least one G allele (adjusted HR 1.95, 95% CI 1.03-3.68). Finally, the combined presence of both favorable genotypes of rs2796267 and rs147788946 had an additional protective effect both on acute rejection (p=0.006) and graft survival (p=0.03). These findings could help to identify patients who could benefit from intensified immunosuppressive therapy or novel complement inhibitory therapeutics.